Pengaruh Dosis Isolat Trichoderma Lokal pada Media Tanam untuk Pertumbuhan Bibit Hibrida Dendrobium discolor >< lasianthera - Sugiyarto Sugiyarto; Tri Suwarni Wahyudiningsih; Ernita Mey Saputri (Universitas Gadjah Mada, 2026)
Research on Trichoderma sp. isolates derived from the roots of the wild orchid Paphiopedilum javanicum for application in commercial orchid acclimatization is still limited. The study aimed to determine the optimal dose of Trichoderma sp. isolates to grow hybrid Dendrobium discolor >< lasianthera seedlings at the acclimatization stage. The study was conducted using a Complete Randomized Block Design (CRBD) with non-factorial experiments and repeated 4 times as blocks. Treatments in the form of Trichoderma sp. doses were 0 g, 2 g, 2.5 g, 3 g, and 3.5 g. Trichoderma sp. doses significantly affected the increase in plant height, the amount of chlorophyll a, and root infection. A dose of 2.46 g was the optimal dose that gave a Trichoderma infection rate in the roots of 100%. A dose of 2.5 g gave the best results in increasing plant height (0.625 cm). A dose of 3.5 g gave the best results in chlorophyll a (4.55 mg/l). Trichoderma has the potential to be propagated into a biofertilizer product to support the growth of commercial orchids during acclimatization.